MoIP-ST: An Instrument to Measure Students’ Problem Solving Skills on Momentum and Impulse - Astuti, Itsna Rona Wahyu; Kaniawati, Ida; Samsudin, Achmad; Suhendi, Endi; Supardiyono, Supardiyono; Suparman, Andreas; Hegarna, Rona; Vera, Rosi (FKIP Universitas Lampung, 2022)
This research aims to develop the MoIP-ST (Momentum and Impulse ProblemSolving Test) instrument to measure students' problem-solving abilities according to the stages of problem-solving skills. The research method used is 4). The research participants were 64 students, consisting of 32 rural and 32 urban 10th-grade students in East Java, who were randomly selected. The first analysis is a multi-rater Rasch measurement based on the results of expert validation, which indicates that item I1 needs improvement. The second analysis is the analysis of the MoIP-ST instrument using the Rasch model, which shows that overall the items on the MoIP-ST are valid and reliable with a Cronbach Alpha of 0.87. The third analysis is the use of the MoIP-ST, which shows that the problem-solving ability of rural students is lower than that of urban students. Student problem-solving needs to be improved through models, methods, learning models, and teaching materials that support problem-solving.Keywords: test instrument, problem solving skills, physics learning.